The influence of the components of the heat transfer coefficient on the efficiency of a low-power tubular heat exchanger - Pelińska-Olko, Ewa; Barnaś, Yessica (Instal, 2021)
Co-flow and counter-flow (WW, WP) heat exchangers of low-power tube-in-tube in configuration 1,2 were tested. Configuration 1 meant the flow of the warmer medium in the inner pipe and colder in the outer pipe, while configuration 2 – the cooler medium in the inner pipe, warmer in the outer pipe. Higher values of the experimental heat transfer coefficient kl, both for WW and WP were observed in configuration 2. In this work, the experimental values of kl were compared with the values calculated with the use of selected theoretical methods. The largest number of theoretical values of kl, consistent with the experiment, for all tested types of exchangers and their configurations, were obtained for the Hausen formula. The coefficient kl includes three components: the element describing the heat transfer from the warmer working medium to the diaphragm, conduction through the diaphragm separating both factors and the transfer of heat from the diaphragm to the cooler medium. The size of this coefficient determines the capacity per 1 running meter of the tube exchanger and thus, together with the average temperature difference of the working media, it affects the heat exchange surface and thus the dimensions of the entire exchanger.